Pengelolaan Konservasi Penyu Sebagai Daya Tarik Wisata Di Pantai Kuta - Uskono, Febryanus Orlando Yoni; Sastrawan, I Gede Anom (JURNAL DESTINASI PARIWISATA; Vol 10 No 1 (2022): VOL 10, NO 1 (2022): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2022)
This study aims to determine the management of turtle conservation as a tourist attraction on Kuta Beach which is in a mass tourism area so it does not threaten the existence of turtle species that lay their eggs on Kuta Beach. How is the development of turtle conservation as a tourist attraction on Kuta Beach that pays attention to the balance between natural resources and tourism activities on Kuta Beach. The type of data used in this study are primary and secondary data types. Data collection techniques used in this study were observation, in-depth interviews, and documentation. The technique of determining informants using purposive sampling. While the data analysis technique uses descriptive qualitative analysis. The results of research conducted that the management of sea turtles conservation as a tourist attraction in Kuta Beach is very unique for domestic and foreign tourists because it is located in the mass tourism area. However, conservation support facilities are inadequate and the need for collaboration between stakeholders, namely the government, non government organization and the community to preserve sea turtles in Kuta Beach from the threat of garbage and wild animals. Keywords: Conservation Management, Sea Turtles, Kuta Beach